Evaluation Report on Working of Community Projects and N. E.S. Blocks Summary Part - I April 1956 - Planning Commission (Planning Commission, 1956)
In the more successful among community projects, there can be no doubt that in terms of provision of basic amenities needed by the people-education, health and sanitation, water supplies, communications-a distinct advance has been made during the project period. Under the rising tempo of development expenditure under the First Five Year Plan, the increase in non-project development expenditure has also been very considerable in most of the project areas.
Planning Commission Programme Evaluation Organisation